Sensible Thought, Coexistence, and the Revolutioanry Impulse to Love - PADILLA, Elaine (Utopía y Praxis Latinoamericana, 2022)
This essay locates the concept of sentido pensante or sensible thought within the recent historical events of the coronavirus pandemic to ask the question on the systems of production of epistemology. It invites the reader, at the insistence of Raúl Fornet Betancourt, to incisively investigate our current masked reality of manufactured consent, to cultivate convivencia, and to make room akin to a trench of ideas for the flourishing of a revolutionary love in our time.